Snake Eyes. A Natural History of Picturing, Perception, and the Serpents That Lurk Within - Yang, Andrew (Captures, 2022)
Snakes capture us like no other creature. As serpents, dragons, and ouroboroi, their potency as symbols complicates their objective portrayal. Meanwhile, research suggests that serpentine shapes are present as ciphers within our visual circuitry before we ever even see them. From traditions of natural history to present-day neurobiology, there may be no way to depict snakes that is not also deeply imaginary.